Analisis Peran Dan Fungsi Komisi C Dalam Menyusun Dana Anggaran Kunjungan Kerja Komisi C DPRD Provinsi Sumatera Utara - Nadia Aprilia; Muhammad Irwan Padli Nasution (Pusat Riset dan Inovasi Nasional, 2023)
In the planning and management of the budget for working visits, Commission C of the North Sumatra Provincial DPRD plays a crucial role. Through qualitative research methods with a descriptive approach and direct observation at the North Sumatra Provincial DPRD for one month, the research findings revealed that Commission C is involved in processes including the preparation, implementation, and distribution of official notes, as well as the printing of documents such as SPT and SPPD for the execution of working visits. Additionally, Commission C also performs legislative, oversight, budgeting, and coordination functions to ensure the efficiency and transparency of fund utilization and compliance with applicable regulations. These findings highlight the significance of the role of Commission C in representing and serving the interests of the North Sumatra community effectively.